Clinical features and prognostic factors in patients with bone metastases from non-small cell lung cancer. Issue 5 (May 2020) - Wu, Xiao-Tian; Zhou, Jian-Wei; Pan, Long-Ci; Ge, Ting
Objective: To investigate the clinical features and evaluate the prognostic factors in patients with bone metastases from non-small cell lung cancer (NSCLC). Methods: We retrospectively investigated 356 patients with NSCLC with bone metastases from January 2012 to December 2017. The overall survival (OS) and 1-year survival rate were calculated by Kaplan–Meier analysis and compared by univariate analysis using the log-rank test. Multivariate analysis was performed using the Cox proportional hazards model. Results: A total of 694 sites of bone metastases were determined among the 356 patients. The most common site of bone metastases was the ribs. The median OS was 12.5 months and the 1-year survival was 50.8% in the overall population. Univariate analysis revealed that histological type, number of bone metastases, Eastern Cooperative Oncology Group performance status (ECOG PS), bisphosphonate therapy, and serum calcium, lactate dehydrogenase, and alkaline phosphatase were significantly correlated with prognosis. Multivariate analysis identified multiple bone metastases, ECOG PS ≥2, lactate dehydrogenase ≥225 U/L, and alkaline phosphatase ≥140 U/L as independent negative prognostic factors. Conclusion: Multiple bone metastases, high ECOG PS, and high serum alkaline phosphatase and lactate dehydrogenase are independent negative prognostic factors for bone metastases from NSCLC.